TINGKAT KEPUASAN MASYARAKAT TERHADAP RESES ANGGOTA DPRA TAHUN 2021 DI DAPIL 1 WILAYAH KOTA BANDA ACEH - Dinda Badzlina; Effendi Hasan; Iqbal Ahmady (Journal of Political Sphere, 2022)
AbstractThe implementation of the recess is the right and obligation of members of the Aceh People's Representative Council (DPRA) to visit, solicit, and follow up on the aspirations and complaints of constituents as well as provide moral and political accountability, which is conveyed during each recess to constituents in their electoral districts. However, what happened is that the recess, this the community has not fully felt the recess activities carried out by DPRA members in gathering aspirations and constituent problems. This is reinforced by the fact that many people still do not know and are not involved in the recess activities carried out by members of the DPRA. This study aimed to determine the level of community satisfaction with the performance of DPRA members during the recess in the 1st electoral district of Banda Aceh City in 2021. This study uses representation theory and the concept of performance measurement. This research used descriptive quantitative research with data collection through questionnaires, observation, and documentation. Data processing in this study uses data editing, transformation, and tabulation methods and is tested using validity tests, reliability tests, and Likert scales. The results showed a low level of community satisfaction in the 1st electoral district of Banda Aceh City on the performance of DPRA members during the recess. As many as 79% of respondents are dissatisfied with the performance of DPRA members in screening aspirations during the 2021 recess. Still, many aspirations are needed by constituents but are not realized. In this case, DPRA members are expected to be more serious in carrying out the recess program, especially fighting for the aspirations of the community, fixing existing problems in the electoral district, and fully realizing the aspirations that were captured during the recess so that the community will benefit from the recess activities.Keywords: DPRA Member Performance, Recess Period, Community Satisfaction